A Study of Utilization Rates of Traditionl Birth Attendants in Phu Wiang District, Khon Kaen Province in Northeast Thailand - Charerntayarak, Lertchai; OUM, Sophal; Ma Yin Nu, Ma Yin Nu; WAISI, Stanley; DAVIES, Carmel; Jirawatkul, Aroon; Saowkontha, Sastri (Journal of Health Science of Thailand, 1993)
An assessment of the use of traditional birth attendants (TBAs) was undertaken in Phu Wiang District, Khon Kaen Province in Northeast Thailand from February to March 1992. The study was cross-sectional using a cluster random sampling scheme with probability proportionate to size. According to official accounts, the utilization of TBA services by mothers has declined, particularly in their role as birth attendants and advisers on family planning. This study set out to substantiate this as well as find out what their new role is now. By questionnaire and in-depth interview it was ascertained that 31% of mothers with children under one had been delivered by TBAs. We found that overall, the utilization of TBAs by women before, during and after delivery were the following: - For antenatal care, 11.4% of mothers and pregnant women (n=248) received either services or advice from TBAs. - For postpartum care, 35% of mothers (n=183) were visited by TBAs. Overall, the proportion of all mothers in the sapled villages who received any advice or services from TBAs at any time last year, i.e. before, during, or after delivery was 79%. The fact that one-third of all deliveries were attended by TBAs in this study provides evidence that the TBA’s influence and acceptability continues to exist amongst people in remote rural areas even when formal health services are made available.